Critiquing “Mainstream Media” on Twitter: Between Moralized Suspicion and Democratic Possibility - Phelan S; Maeseele P (USC Annenberg Press, 2023)
How can we understand the critique of mainstream media (MSM) in a political moment where intense suspicion of media and journalism has been normalized in reactionary discourses? This article addresses this question from a discourse theoretical perspective that is supported by a corpus-assisted interpretivist analysis of how the terms “MSM” and “mainstream media” were articulated in a January 2021 sample of more than 11,000 tweets from different time zones. We begin by clarifying the political stakes of our argument and situating the historical emergence of “mainstream media” as a discursive category. Our Twitter analysis highlights the “logic of equivalence” established between mainstream media and other identities and the normalization of a moralized representation of media as a corrupt ally of government. We conclude by speculating on how we might affirm a radical democratic conception of media critique in a cultural context where anti-MSM rhetoric can float easily between different discourses and ideologies.
Keywords: critique; discourse theory; hermeneutics of suspicion; logic of equivalence; mainstream media; moralized rhetoric; reactionary politics